Application of the microarray technology to the transcriptional analysis of muscle phenotypes in pigs. (27th March 2014) - Pena, R. N.; Quintanilla, R.; Manunza, A.; Gallardo, D.; Casellas, J.; Amills, M.
Summary The transcriptome refers to the collection of all transcripts present in a cell. Gene expression has a very dynamic nature; it acts as a bridge between epigenetic marks, DNA sequence and proteins and changes to accommodate the requirements of the cell at each given time. Recent technological advances have created new opportunities to study complex phenotypes from a global point of view. From an animal production perspective, muscle transcriptomics has been investigated in relation to muscle growth, carcass fattening and meat quality traits. In this review, we discuss the impact of nutritional, anatomical and genetic factors on muscle gene expression and meat quality of pigs assessed by microarray technologies. Altogether, several common themes have been revealed by the in‐depth analysis of the current body of knowledge, for instance, the involvement of genes related to energy balance and substrate turnover in the oxidative/glycolytic phenotype of red/white muscle fibre types and in the storage of intramuscular fat. The review also covers recent advances in the discovery of expression QTL and regulatory RNAs in porcine breeds as well as technical developments in the field of deep‐sequencing technologies that are expected to substantially increase our knowledge about the genetic architecture of meat quality and production traits.